Implementasi Sistem Informasi Akuntansi Dan Administrasi Berbasis Digital - Alfian, Mohammad; Kartika, Dewi; Ferida, Arifany (DIKEMAS (Jurnal Pengabdian Kepada Masyarakat), 2022)
Villages have the opportunity to develop their potential since the enactment of the Village Law. Optimizing the potential of the village is used for the benefit of the village community. The purpose of optimizing the potential of the village is to improve the lives of the village community. The purpose of establishing Village-Owned Enterprises (BUMDes) is one of the government's efforts to drive the village economy. BUMDes is expected to be a locomotive for the movement of the village economy that can make the village prosperous and reduce poverty. For this goal to be achieved, BUMDes needs to be managed professionally so that they can compete and develop properly. BUMDes Bangun Ber Bersama is a BUMDes in Kepunduhan Village, Tegal Regency. BUMDes Bangun Bersama has the full support of the local village government. BUMDesa Bangun together has limited capabilities of existing human resources. The limitation of existing human resources is the ability in financial reporting operational activities. This Community Partnership Program (PKM) aims to provide financial management methods from manual to systematic and digitalized based on Google Suite. The output of the activities carried out is that BUMDes administrators understand the Bumdes administration system and accounting/bookkeeping and have the ability to make BUMDes Financial Statements in the form of simple accounting, namely making daily cash books, balance sheets, profit and loss reports, and digital-based and systematic capital change reports.